2014
DOI: 10.1002/jbmr.2221
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Bone Density, Microstructure, and Strength of the Distal Radius in Male Patients With Rheumatoid Arthritis: A Case-Control Study With HR-pQCT

Abstract: In this cross-sectional study, we investigated volumetric bone mineral density (vBMD), bone microstructure, and biomechanical competence of the distal radius in male patients with rheumatoid arthritis (RA). The study cohort comprised 50 male RA patients of average age of 61.1 years and 50 age-matched healthy males. Areal BMD (aBMD) of the hip, lumbar spine, and distal radius was measured by dual-energy X-ray absorptiometry. High-resolution peripheral quantitative computed tomography (HR-pQCT) of the distal rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 60 publications
4
20
0
Order By: Relevance
“…We have reported alterations in the density and microstructure of the cortical bone of patients with RA . Rossini et al had also observed that low BMD at the cortical site was significantly associated with the presence of bone erosions .…”
Section: Discussionmentioning
confidence: 55%
“…We have reported alterations in the density and microstructure of the cortical bone of patients with RA . Rossini et al had also observed that low BMD at the cortical site was significantly associated with the presence of bone erosions .…”
Section: Discussionmentioning
confidence: 55%
“…On the other side, from the bone point of view, we previously observed that low bone mineral density (BMD) at the cortical site was significantly associated with the presence of bone erosions,8 and recently Zhu and colleagues reported alterations in the density and microstructure of the cortical bone of patients with RA, providing new insight into the microstructural basis of bone involvement in RA 9. In particular, in patients with anticitrullinated protein antibodies, cortical thinning might be present even before the clinical onset of RA and it seems strictly related with the risk of bone erosions 10…”
mentioning
confidence: 99%
“…Male patients with rheumatoid arthritis as another representative of a pro‐inflammatory disease suffer from altered trabecular microstructure, increased cortical porosity, and cortical pore volume . In our study population, these cortical indices measured at the radius and later at the tibia increased over time, whereas no differences were observed in the control population.…”
Section: Discussionmentioning
confidence: 63%